A new species of stygobiont freshwater planarian (Platyhelminthes, Tricladida) from a chemoautotrophic ecosystem: the Frasassi karst in Italy - Stocchino, Giacinta Angela; Sluys, Ronald; Montanari, Alessandro; Manconi, Renata (Zootaxa, 2017)
In this paper we report a new species of Dendrocoelum from the chemoautotrophic ecosystem of the Frasassi hypogenic cave complex in the northeastern Apennines of Italy. Dendrocoelum leporii Stocchino & Sluys, sp. nov. is characterized by the presence of a muscular atrial valve, which is unique within the genus. Moreover, the new species is characterized also by a penis papilla with a pseudoflagellum, numerous testes situated in the ventral, dorsal and median body regions with the follicles extending to the far posterior end of the body, and a large adenodactyl with the so-called Balkan type of musculature. The new species represents the twelfth dendrocoelid species recorded for Italy. A summary is provided of the species of the family Dendrocoelidae Hallez, 1892 thus far reported for the mainland and the isles of Italy.